Evaluation of the Graft Kidney in the Early Postoperative Period: Performance of Contrast‐Enhanced Ultrasound and Additional Ultrasound Parameters. (12th November 2020) - Goyal, Ankur; Hemachandran, Naren; Kumar, Atin; Sharma, Raju; Shamim, Shamim Ahmed; Bansal, Virinder Kumar; Das, Chandan Jyoti; Kandasamy, Devasenathipathy; Agarwal, Sanjay Kumar; Dinda, Amit Kumar; Seenu, V.
Abstract : Objectives: To evaluate the various quantitative parameters of Doppler ultrasound, contrast‐enhanced ultrasound (CEUS), and shear wave elastography (SWE) of graft kidneys in the early postoperative period and to explore their utility in the diagnosis of parenchymal causes of graft dysfunction. Methods: In this ethically approved study, consecutive patients who underwent renal transplantation from March 2017 to August 2018 were recruited, and those with urologic or vascular complications and those who denied consent were excluded. All patients underwent ultrasound with Doppler, SWE, CEUS (using sulfur hexafluoride), and renal scintigraphic examinations 3 to 10 days after transplantation. A composite reference standard was used, including the clinical course, renal function test results, urine output, and histopathologic results for graft dysfunction. Cortical SWE values, quantitative CEUS parameters (generated from a time‐intensity curve), and their ratios were analyzed to identify graft dysfunction and differentiate acute tubular necrosis (ATN) from acute rejection (AR). Results: Of the 105 patients included, 19 developed graft dysfunction (18.1%; 12 ATN, 5 AR, and 2 drug toxicity) in the early postoperative period. The peak systolic velocity in the interpolar artery showed a significant difference between control and graft dysfunction groups ( P  < .001) as well as between ATN and AR ( P  = .019). Resistive indices and SWE did not show significant differences. Ratios of the time to peak showed a significant difference between control and graft dysfunction groups ( P  < .05). The rise time and fall time of the large subcapsular region of interest and the rise time ratio were significantly different between ATN and AR ( P  = .03). Conclusions: Contrast‐enhanced ultrasound can be used to diagnose parenchymal causes of early graft dysfunction with reasonable diagnostic accuracy. Abstract : Access the CME test here and search by article title.